Electricity from the Silk Cocoon Membrane - Tulachan, Brindan (Nature Publishing Group, 2014)
Silk cocoon membrane (SCM) is an insect engineered structure. We studied the electrical properties of mulberry (Bombyx mori) and non-mulberry (Tussar, Antheraea mylitta) SCM. When dry, SCM behaves like an insulator. On absorbing moisture, it generates electrical current, which is modulated by temperature. The current flowing across the SCM is possibly ionic and protonic in nature. We exploited the electrical properties of SCM to develop simple energy harvesting devices, which could operate low power electronic systems. Based on our findings, we propose that the temperature and humidity dependent electrical properties of the SCM could find applications in battery technology, bio-sensor, humidity sensor, steam engines and waste heat management.